A Silicon Nanowire‐Based Electrochemical Sensor with High Sensitivity and Electrocatalytic Activity. (8th February 2013) - Su, Shao; Wei, Xinpan; Guo, Yuanyuan; Zhong, Yiling; Su, Yuanyuan; Huang, Qing; Fan, Chunhai; He, Yao
<x xml:space="preserve">Abstract</x> A new kind of silicon nanowire (SiNWs)‐based nanoelectrode assembly, a gold‐nanoparticle‐decorated silicon nanowire array (AuNPs@SiNWsAr), is employed for the construction of high‐performance electrochemical sensors. Significantly, the electrochemical nanosensors are capable of sensitive detection of various electroactive molecules (e.g., dopamine (DA), ascorbic acid (AA), hydrogen peroxide (H2O2), and glucose). Further, DA molecules loaded on the surface of AuNPs@SiNWsAr preserve stable high electroactivity overnight without special protection, while free DA molecules may lose their biological activity due to severe oxidization in ambient environment. These findings may offer new opportunities for the design of high‐performance electrochemical nanosensors with high sensitivity and robust stability.